Cerebral malaria: a lethal complication of a common tropical infection - Parasher, Anant; Chowdhary, Rupak; Bez, Jeplin (International Journal of Research in Medical Sciences, 2021)
Cerebral malaria (CM) represents a deadly neurological complication associated with Plasmodium falciparum infection. It is defined as an unarousable coma or a deep level of unconsciousness in the presence of a P. falciparum parasitemia, the diagnosis confirmed after exclusion of other common causes of coma such as hypoglycemia, septicemia, metabolic derangements and bacterial and viral meningitis/encephalopathies. Mortality is high and some surviving patients sustain neuronal injury which manifests as long-term neuro-cognitive impairments. Microscopy of Giemsa-stained blood smears remains the gold standard for confirmation of malaria diagnosis. The purpose of this review was to summarize the updated knowledge on the disease, its presentation, complications and neurological sequelae and the presently available newer and experimental adjuvant therapies. For this review, a PubMed search was conducted for articles and case reports from 1968 to 2020 containing the keywords cerebral malaria, P. falciparum, neurological impairment, neurocognitive defects and artesunate combination therapy. The treatment includes specific antimalarial therapy, supportive therapy for multi-organ dysfunction and management of associated complications. Prompt and rapid stabilization of the patient, adequate fluid supplementation and correction of electrolyte imbalance remain the most vital supplementary interventions in these cases, along with early induction of primary parenteral antimalarial therapy in the form of artemisinin based combination therapy (ACT) or quinine. Neurological sequelae including seizures are frequently observed in many treated and recovered cases, with some patients having to endure long term neurocognitive defects.